2009
DOI: 10.1016/j.molcel.2009.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Global Regulatory Perturbations across Human Cancers

Abstract: Summary The discovery of pathways and regulatory networks whose perturbation contributes to neoplastic transformation remains a fundamental challenge for cancer biology. We show that such pathway perturbations, and the cis-regulatory elements through which they operate, can be efficiently extracted from global gene-expression profiles. Our approach utilizes information-theoretic analysis of expression levels, pathways, and genomic sequences. Analysis across a diverse set of human cancers reveals the majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
259
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(278 citation statements)
references
References 50 publications
9
259
0
Order By: Relevance
“…4D, right panel). And lastly, we also analyzed the RNAseq data with the iPAGE gene expression analysis tool (42). This analysis identified the unfolded protein binding function as being significantly up-regulated in three out of four primary AML specimens treated with PDT (supplemental Fig.…”
Section: Pdt Regimen Does Not Affect Nf-b Signaling But Induces Stronmentioning
confidence: 99%
“…4D, right panel). And lastly, we also analyzed the RNAseq data with the iPAGE gene expression analysis tool (42). This analysis identified the unfolded protein binding function as being significantly up-regulated in three out of four primary AML specimens treated with PDT (supplemental Fig.…”
Section: Pdt Regimen Does Not Affect Nf-b Signaling But Induces Stronmentioning
confidence: 99%
“…The CCAAT-box, regarded as a binding site for NF-Y, was recently found to be a common cis-regulatory motif in the promoters of genes up-regulated in pluripotent stem cells (30), and it was also highly enriched in regulatory regions of genes overexpressed in tumors (31). Subunit NF-YA has two different isoforms, NF-YAL (long) and NF-YAS (short), resulting from alternative splicing (24).…”
Section: Discussionmentioning
confidence: 99%
“…More tellingly, de novo motif discovery methods that allow unbiased identification of sequence logos showed that promoters of genes, specifically overexpressed in tumors, are significantly enriched in Y/CCAAT elements. [32][33][34] This indicates that Y/CCAAT is of importance in the overexpression of cancer genes in tumors. Therefore, the TFs recognizing this element are likely relevant for the process of cellular transformation.…”
Section: Y and Ccaat: Two Names One Entitymentioning
confidence: 98%